2022
DOI: 10.32493/jee.v4i4.22023
|View full text |Cite
|
Sign up to set email alerts
|

Peran Inovasi Produk dan Evolusi Sosial Dalam Penciptaan Kesejahteraan Nasabah Bank Wakaf Mikro

Abstract: Optimalisasi inovasi produk membutuhkan perubahan pelaku usaha mikro dalam meningkatkan kesejahteraannya secara berkelanjutan. Penelitian untuk menganalisis inovasi produk nasabah bank wakaf mikro dengan pendekatan model evolusi sosial. Metode penelitian menggunakan kualitatif dengan pendekatan grounded theory. Pengumpulan data dari observasi, wawancara, dokumentasi dan studi pustaka. Analisis menggunakan design thingking dengan teknik triangulasi. Penelitian bertempat di bank wakaf mikro An-Nawawi Tanara Kabu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Micro Waqf Bank is a sharia microfinance institution that focuses on financing small communities with a profit-sharing pattern, and this institution is purely for financing (Balqis & Sartono, 2020). Several studies were found to have discussed a lot regarding Micro Waqf Banks in alleviating poverty based on pesantren (Fauzi & Widana, 2022;M. Daim et al, 2021;Putra & Zaki, 2020;Siska Lis Sulistiani et al, 2019).…”
Section: • Cluster 4 Discusses the Theme Of Micro Waqf Bank (Bwm)mentioning
confidence: 99%
“…Micro Waqf Bank is a sharia microfinance institution that focuses on financing small communities with a profit-sharing pattern, and this institution is purely for financing (Balqis & Sartono, 2020). Several studies were found to have discussed a lot regarding Micro Waqf Banks in alleviating poverty based on pesantren (Fauzi & Widana, 2022;M. Daim et al, 2021;Putra & Zaki, 2020;Siska Lis Sulistiani et al, 2019).…”
Section: • Cluster 4 Discusses the Theme Of Micro Waqf Bank (Bwm)mentioning
confidence: 99%
“…Increasing marketing of customer products (Fauzi & Widana, 2022a). They increase social innovation in customer businesses (Fauzi & Widana, 2022b). However, from various studies and research on micro waqf banks, there is no or still limited information on how most female customers avoid loan sharks.…”
Section: Introductionmentioning
confidence: 99%